(untitled) (TEL Tempo, Espaço e Linguagem, 2026)
Clarice Lispector and Plínio Marcos made literature a radical way of being astonished by "reality," creating experiences "with" the real in the years 1962 and 1977, respectively. Blurring the boundaries between History and Literature, I analyze the forms of literary composition in the short stories "Mineirinho" and "Inútil Canto e Inútil Pranto pelos Anjos Caídos," problematizing literature as a way of sharing the sensible in the endless task of critiquing violence and its effects.